Community knowledge, attitudes, and practices about toxoplasmosis in Unguja Island, Tanzania (Journal of Ideas in Health, 2024)
Background: Toxoplasmosis is among the globally neglected zoonotic diseases caused by Toxoplasma gondii. Humans get infected after ingesting or coming into contact with oocysts from the feces of infected cats. Illiteracy about the infection is one of the significant risk factors for its transmission. The study aimed to determine the community knowledge, attitudes, and practices that influence toxoplasmosis transmission in Unguja Island, Zanzibar, Tanzania.Methods: The study used a cross-sectional design, which was done from February to April 2023. Semi-structured questionnaires collected data on 139 respondents' demographics, practices, knowledge, and attitudes regarding toxoplasmosis. The chi-square test was used to assess the statistical association between variables at a p-value of < 0.05.  Results: Out of 139 recruited respondents, only 18.0% of respondents were aware of Toxoplasmosis. The study revealed several risk factors for Toxoplasmosis transmission, whereby 63.1% of the cat owners didn't deworm their cats regularly, 70.8% didn't clean the cat kennels, and 53.1% didn't wash their hands after cleaning kennels and touching a cat. Furthermore, out of all respondents, about two-thirds didn't drink treated water and 87.8% ate raw vegetables as salads. The study revealed both negative and positive attitudes concerning Toxoplasmosis, where 64.7% of respondents thought that cats cannot transmit pathogens to humans and 66.2% did not agree with people interacting with stray cats, respectively. There was an association of awareness of the disease's existence with high education levels (P value = 0.001) and sex (females) (P = 0.002).Conclusion: The study revealed a low awareness of the existence of the infection despite the higher interaction of cats with humans in the study area. We recommend the provision of public health education focusing on how the disease is transmitted, the relationship of the disease with cats, the management of cat feces, clinical signs of the disease, its treatment, and control.
Keywords: Attitude, Practices, Knowledge, Toxoplasmosis, Unguja Island, Zanzibar, Tanzania